PHYTOCHEMICAL COMPOUND LEVELS IN BAMA LEAF EXTRACT AND ITS INHIBITORY ACTIVITY AGAINST Salmonella Thypimurium ATCC 19430 - Suryaningsih, Putu Ayu; Oka Suyasa, Ida Bagus; Fridayanti, Komang Dewi (Meditory : The Journal of Medical Laboratory, 2023)
Diarrhea is one of the intestinal infection symptoms that can cause poor absorption to loss of nutrition if not treated immediately. Salmonella spp. is 1 of the 4 fundamental global causes of diarrhoeal diseases and antibiotics have been widely used to treat infections caused by this group of bacteria. WHO reported that the antibiotic resistance of Salmonella spp. has increased in past years. For those reasons, efforts have been made to discover new antimicrobial compounds from various sources, including the ethanol extracts of Bama leaves. Therefore, this study aimed to determine the phytochemical compounds (flavonoids, tannins, and phenols) in the ethanol extract of Bama leaves and their inhibitory effect against the bacteria Salmonella typhimurium which causes diarrhea. Design method used is RAL 5 x 4, 5 treatments were concentration of Bama leaf extract 6,25%, 12,5%, 25%, 50% and 75% and 4 replicates for each test. The phytochemical quantitative analysis showed bama leaf extract had 520,99 mgQE flavonoid / 100 gram, 1465,19 mgTAE tannin/100 g and 16531,78 phenol/100 g extract. All contrentration of bama leaf extract could not inhibit the growth of Salmonella thypimurium ATCC 19430.